Quercetin Enhances Endurance Capacity via Antioxidant Activity and Size of Muscle Fibre Type 1 - Leelayuwat; S. Laddawan; Y. Kanpetta; M. Benja; D. Wongpan; O. Tunkamnerdthai; J. Wattanathorn; S. Muchimapura; J. Yamauchi (Journal of Pharmacy and Nutrition Sciences, 2012)
This study aimed to examine effects of quercetin on 1) endurance capacity 2) malondialdehyde (MDA) and superoxide dismutase (SOD) activity in skeletal muscle and 3) muscle fibre density and size in mice after an intense exercise. There were 5 groups: control, vitamin C (250 mg/kg body weight), quercetin 150, 300, and 450 mg/kg body weight respectively once a day for 28 days. Endurance capacity was measured by exhaustive swimming exercise test which was done 24-h after swimming at high intensity. Then muscles were analyzed for MDA, SOD activity, and muscle fibre density and size. After the 28-day treatment, endurance time in vitamin C and quercetin treated groups at dose of 150 mg/kg body weight were longer than the vehicle group (p<0.05). MDA concentration in extensor digitorum longus muscle was lower than vehicle group in vitamin C, Q150 and Q450 groups and in soleus muscle the highest was in Q300 group. SOD activity in soleus muscle in Q150 group was higher than vitamin C and Q450 groups. Significant increase in cell diameter of soleus muscle was found (p<0.05). Current findings suggest that ingestion of quercetin can improve endurance capacity, due probably to increased antioxidant activity and size of muscle fibre type 1.